Restoration of external urethral sphincter function after pudendal nerve end-to-end anastomosis in the male rabbit - Martínez y Portillo, Francisco-José; Osmonov, Daniar Kurmanbekovich; Seif, Christoph; Braun, Peter-Martin; Boehler, Georg; Alken, Peter; Jünemann, Klaus-Peter (The journal of urology, 2004)
Purpose: - - In this study we rehabilitated external urethral sphincter function by pudendal nerve end-to-end anastomosis after experimental pudendal nerve axotomy in male rabbits. - - Materials and Methods: - - A total of 17 animals were included in this study, including group 1—a control group of 5 (29.4%), group 2—6 (35.3%) and group 3—6 (35.3%). Animals from group 2 underwent bilateral axotomy and group 3 underwent pudendal nerve end-to-end anastomosis. In all groups we performed urodynamic investigations prior to axotomy, after axotomy or anastomosis, and 14, 42 and 90 days after axotomy or nerve anastomosis. - - Results: - - In untreated group 1 control sphincter pressure was 28.5 cm H2O. In group 2 average urethral sphincter pressure was 5.6 cm H2O 14 days after axotomy with only a slight increase to 11.05 cm H2O by day 90. In group 3 external urethral pressure increased to 8.26 cm H2O after 14 days and to 21.32 cm H2O by postoperative day 90. - - Conclusions: - - External urethral sphincter deficiency after bilateral pudendal nerve axotomy demonstrates the primacy of the pudendal nerve in the innervation of the external urethral sphincter. We were able to rehabilitate external urethral sphincter function by performing pudendal nerve end-to-end anastomosis.